PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN UMUM DAERAH (PERUMDA) AIR MINUM TIRTAULI KOTA PEMATANG SIANTAR - Sitanggang, Jogi Lubuk; Safrin, Feby Aulia (Jurnal Ilmiah Wahana Pendidikan, 2024)
Increasingly competitive competition makes companies must be able to increase their competitiveness to maintain the company's survival. One of the efforts that can be made is to improve employee performance. The success and failure of improving employee performance are determined by leadership, namely an effective leadership style that will impact the progress of the company and work motivation, which supports efforts to improve the quality of employee work to boost employee performance. This study aims to determine the effect of transformational leadership and work motivation on employee performance at the Regional Public Company (Perumda) Tirtauli drinking water in Pematang Siantar City. This form of research is quantitative research with an associative approach. The population in this study were all employees of Perumda Tirtauli of Pematang Siantar city. The sampling technique used is non-probability sampling with simple random sampling. The analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analyses, partial tests, simultaneous tests and coefficient of determination tests. The results of this study indicate that the transformational leadership variable has a positive and significant effect both partially and simultaneously on the performance of Perumda Tirtauli employees in the city of Pematang Siantar, with an effect of 76.6%. In comparison, other factors outside this research model influence the remaining 23.4%.